Reproductive tract infections among geriatric population in a block of West Bengal: knowledge and risk behaviour assessment - Ray, Kuntala; Pattanayak, Shalini; Naskar, Somnath; Basu, Mausumi (Intelektual Pustaka Media Utama, 2025)
Reproductive tract infections (RTIs) among the geriatric population remains neglected, causing increase in morbidity. This study aimed to elicit knowledge, identify risk behaviour for RTIs among the elderly residing in a block of West Bengal, to determine any associations between sociodemographic profile with knowledge and risk behaviour respectively, and to assess any correlation between knowledge and risk behaviour. A community-based study was conducted using multistage sampling, among 158 geriatric residents of a rural block in West Bengal, India for a period of 3 months in 2023. Face-to-face interviews were carried out using an interview schedule. Overall median scores were calculated separately for knowledge and risk behaviour domains. Score < median score was categorized as ‘inadequate knowledge’ and score ≥ median was classified as ‘high risk’ behaviour. Nearly 30% reportedly had ‘inadequate knowledge’ while 77% had ‘high risk’ behavior for RTIs. Higher odds of inadequate knowledge and high-risk behavior were observed among those who were employed and those who availed of any social security scheme(s). Moderately positive correlation was obtained between knowledge and risk behavior.